Dual orexin receptor antagonists as promising therapeutics for Alzheimer’s disease - S. M. Ragsdale; J. M. Radovich; I. I. Coiduras; W. V. McCall; S. C. Grant; C. Lee; A. Wilber (npj Biological Timing and Sleep)
Abstract We examine the relationship between sleep, glymphatics and Alzheimer’s disease (AD), and recent work questioning glymphatic clearance during sleep. We highlight a need for understanding glymphatic and/or other mechanism of clearance during sleep, and review glymphatic flow measurement methods. Further, we explore dual orexin receptor antagonists (DORAs) potential to mitigate AD sleep disturbances and enhance clearance. Further research could elucidate a linkage between DORAs, improved sleep and reducing AD pathophysiology.